(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Today, international arbitration is the most widely used alternative dispute resolution method to resolve commercial disputes between parties. International commercial arbitration is considered a consequence of party agreement as it crucially depends on the parties’ agreement to resolve disputes through private adjudication by a single arbitrator, or a tribunal consisting of more than one, appointed in accordance with rules of a specific arbitration institution that the parties themselves have agreed to adopt, usually by including an arbitration clause in their contract. The practice of international arbitration has thus developed in a manner to allow parties from different linguistic, legal and cultural backgrounds to resolve their disputes with minimum interference from the courts. In arbitration, parties or their representatives, often legal counsels, present a dispute to an impartial single arbitrator or an arbitration tribunal to issue an award, which is binding for the disputing parties. The award is generally non-appealable in a court of law. In arbitration, the parties at dispute have considerable input in the selection of the arbitration tribunal, and also in the choice of processes and procedures they would like the tribunal to follow, including the choice of language, the seat of arbitration, as well as the arbitration rules according to which the resolution is negotiated.